Sigmoid fixation associated with rectopexy using a laparoscopic approach could prevent relapse of rectal prolapse in pediatric patients with spinal dysraphia - Montes Tapia, Fernando Félix; Cura Esquivel, Idalia Aracely; Garza Luna, Ulises; Martínez Flores, Guillermo; Muñoz Maldonado, Gerardo Enrique; Abrego Moya, Valdemar (W.B. Saunders Co., 2008)
Recurrent rectal prolapse, resistant to medical treatment, is an indication for surgical treatment. Patients with spinal dysraphia frequently have already been treated by sclerotherapy or other surgical techniques, but unsuccessfully. Methods: We present 2 patients, who underwent laparoscopic rectopexy, with spinal dysraphia and complete rectal prolapse relapse after conservative treatment. In these patients, we performed, as an additional technique, fixation of the rectosigmoid to avoid recurrence by invagination or prolapse of the anterior wall. Results: Follow-up at 14 and 11 months, respectively, did not find any recurrence. Conclusion: We suggest that laparoscopic rectopexy with sigmoid fixation should be considered as an alternative for the treatment for patients with spinal dysraphia and rectal prolapse to avoid recurrence.